The Virtual Screening to Search Proplasmepsin II Inhibitor from Indonesian Medicinal Plant Phytochemicals: Anti-Malaria - Muhammad Habiburrohman; Wilda Nur Rohmatilah; Arthur Hariyanto Prakoso; Bawon Triatmoko; Ari Satia Nugraha (Future Science)
The indigenous people of Indonesia have used medicinal plants to survive infectious diseases, including malaria. The knowledge has been passed through the generation and a limited number of the plants have been studied properly. Malaria infection has been an endemic and complicated problem in the archipelago where drug-resistant cases worsen the situation. Natural product study without pharmacological information has been a drawback to the development of natural-based antimalarial. Computational chemistry protocol gives lower cost facilitation to later a conventional in vitro bioassay. In this study, virtual screening was deployed to find a Proplasmepsin II enzyme inhibitor, in which the enzyme plays an important in this parasite metabolism. The enzyme (1PFZ) was collected from the PDB database followed by docking validation before exhaustive docking calculation of 238 compounds from 43 Indonesian medicinal plants. The docking protocol was valid as indicated by rmsd value of 1.275 Å. One top hit molecule, AM56, was gained with its free energy of binding value of 10.8 kcal/mol which is better than the interaction of the native ligand, propane-1,2,3-Triol, with the free energy of binding ( G) score of 3.9 kcal/mol. AM56 was a secondary metabolite of Borassus flabellifer and its anti-plasmodium was previously studied. However, the mechanism of action of AM56 was never been reported. This study was able to discover a molecular scaffold of proplasmepsin II enzyme inhibitor and can be used as a pathway to QSAR study of AM56 semi-synthetic derivatives.